Supernatural. Season five [videorecording (DVD)] - Padalecki, Jared, 1982-; Ackles, Jensen (Warner Home Video, 2010)
Two brothers and one fallen angel, against all the might of Satan and his army! As the Apocalypse grows closer, threatening to turn Earth into a battlefield soaked with human blood, Sam, Dean, and Castiel struggle against daunting odds. New foes arise, including the Four Horsemen of the Apocalypse. Season Five follows Sam and Dean on their most terrifying journey yet, one that may lead them to the only ally strong enough to defeat the Devil: God.